Kepatuhan Pemerintah Kota Makassar terhadap Pemenuhan Standar Pelayanan Publik oleh Ombudsman RI Perwakilan Sulawesi Selatan - Restu Mayang Sara Nur (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Public service is one of the main indicators in assessing the implementation of government oriented towards the principles of good governance. In the Indonesian context, provisions regarding the government's obligation to provide accessible, effective, measurable, and responsive services have been stipulated in Law Number 25 of 2009 concerning Public Services. However, findings by the Ombudsman of the Republic of Indonesia indicate that the level of compliance of government agencies, particularly local governments, with public service standards remains inconsistent. This study aims to evaluate the extent to which the Makassar City Government meets public service standards in accordance with statutory provisions and to identify internal and external factors influencing their implementation. This study uses a qualitative approach with descriptive analysis, located in Makassar City at the Manpower Office and the South Sulawesi Representative Office of the Ombudsman of the Republic of Indonesia. Informants were selected purposively through in-depth interviews and observations, then the data were analyzed through the stages of reduction, presentation, and drawing conclusions. The results of the study indicate that the fulfillment of service standards has not been fully achieved. This condition is influenced by limited human resources, leadership variables, policy complexity, and minimal community involvement. This research is expected to be a reference in strengthening public service policies by increasing compliance with service standards.